Pengaruh Return on Asset dan Intensitas Asset Tetap terhadap Penghindaran Pajak (Tax Avoidance) pada Perusahaan Manufaktur Bidang Usaha Konstruksi yang Terdaftar di BEI Periode Tahun 2021 - 2023 - Okky Kharisma; Saridawati Saridawati (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This research aims to review, Return on Asset and the Intensity of Assets on tax avoidance in manufacturing companies in the construction sector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The independent variables used in this study are Return on Asset (ROA) and Intensity of Assets (CAPIN), while the dependent variable in this study is Tax Avoidance which is measured based on the ETR ratio. The research method used is quantitative descriptive with a multiple linear regression approach through descriptive statistical tests, classical assumption tests, and hypothesis tests. The research sample was determined using a purposive sampling technique with a total of 13 companies and 39 observation data. The results of the study indicate that ROA has a negative and significant effect on tax avoidance, while CAPIN has no effect on tax avoidance. Simultaneously, both variables also have a significant effect on tax avoidance.